2008
DOI: 10.1017/s0963548308008948
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Percolation Mixing Time

Abstract: We provide an estimate, sharp up to poly-logarithmic factors, of the asymptotic almost sure mixing time of the graph created by long-range percolation on the cycle of length N (Z/NZ). While it is known that the asymptotic almost sure diameter drops from linear to poly-logarithmic as the exponent s decreases below 2 [4,9], the asymptotic almost sure mixing time drops from N 2 only to N s−1 (up to poly-logarithmic factors).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…Although arising from questions in mathematical physics , the problem was recognized quickly to pose interesting challenges for probability . More recently, instances of long‐range percolation have been used as an ambient medium for other stochastic processes (e.g., ). The overarching theme here is the geometry of random networks.…”
Section: Introductionmentioning
confidence: 99%
“…Although arising from questions in mathematical physics , the problem was recognized quickly to pose interesting challenges for probability . More recently, instances of long‐range percolation have been used as an ambient medium for other stochastic processes (e.g., ). The overarching theme here is the geometry of random networks.…”
Section: Introductionmentioning
confidence: 99%
“…In [1], the discontinuity of the percolation density at s = 2 is shown. In the recent study in [8] , long range percolation mixing time is considered and it is shown that the order of the mixing time changes discontinuously when s = 2. In [18], estimates of effective resistance are given for general d, s, and the discontinuity mentioned in (1) is shown in a sense of effective resistance.…”
Section: Framework and Main Resultsmentioning
confidence: 99%
“…Lemma 8. 5 We have that, Proof. It is enough to prove the converge of 1 t N A,M t for a single pair (A, M) with the extension to uniform convergence over all pairs following by discretising the space.…”
Section: Lemma 81mentioning
confidence: 97%
“…This paper crucially makes use of the transience results established therein. Benjamini, Berger and Yadin [5] study the spectral gap τ of SRW on Z/NZ, providing bounds of the form cN s−1 ≤ τ ≤ CN s−1 log δ N, in that case that nearest neighbor connections exist with probability 1.…”
Section: Introductionmentioning
confidence: 99%